Retrospective study of perioperative cardiac arrest from a Chinese tertiary hospital. Issue 32 (13th August 2021) - Kan, Huili; Ding, Yonghong; Wu, Shanshan; Zhang, Zongwang
Abstract : Abstract: Studies on perioperative cardiac arrest in Chinese hospitals have rarely been retrieved from international journals. This survey evaluated the incidence, causes, and outcomes of perioperative cardiac arrests in a Chinese tertiary general hospital between July 2013 and December 2020. The incidence of cardiac arrest within 24 hours of anesthesia administration was retrospectively identified using an anesthesia database in Liaocheng People's Hospital. During the study period, there were 118, 152 anesthetics. Data collected included patient characteristics, surgical procedures (elective or emergency), American Society of Anesthesiologists (ASA) physical status score, type of surgery, anesthesia technique, and outcome. Cardiac arrests were grouped into one of 3 groups: totally anesthesia-related, partially anesthesia-related, or anesthesia-unrelated. In total, 41 cardiac arrests (3.5:10, 000) and 26 deaths (2.2:10, 000) were found. Major risk factors for cardiac arrest were children under 1 year, adults between 19 and 65 years, and the elderly (>80 years) ( P  < .001), male patients ( P  = .02), emergency surgery ( P  < .001), and ASA grade V patients without anesthesia ( P  = .009). There were 19 anesthesia-related cardiac arrests (1.6:10, 000) – 2 were totally related, and 17 were partially related to anesthesia. There were 9 anesthesia-related deaths (0.8:10, 000), all of which were partially related to anesthesia. Perioperative cardiac arrests were correlated with age, gender, ASA grade and surgical procedures. The 2 most important patient factors leading to cardiac arrest were hemorrhagic shock from trauma and septic shock, respectively.